Adaptasi dan Validasi Awal Skala Sistem Kerja Terintegrasi Kesejahteraan dan Kinerja Tinggi di Indonesia - Tri Rahayungngsih; Nelia Afriyeni (Jurnal Ilmu Perilaku, 2025)
In a competitive workplace, companies are not only required to increase employee productivity but also to ensure their well-being. High-Performance Work Systems (HPWS) have long been used to improve organizational efficiency and performance. However, their implementation is often associated with excessive work pressure, which can negatively impact employee mentality. The urgency of this research stems from the need to develop an integrated HPWS focused on employee well-being, namely the High Well-Being Performance Work Systems (HWBPWS) model. However, existing studies and measurement tools have been developed primarily in Western contexts, raising cultural and contextual concerns for their application in Southeast Asia. This study aims to adapt and validate the HWBPWS scale for the Indonesian workforce. This adaptation followed the International Testing Commission (ITC) guidelines, including translation, expert review, and readability testing. The measurement model was tested using PLS-SEM with the assistance of SmartPLS 4 software. Evaluation of the measurement model included testing convergent validity, internal reliability, and discriminant validity. Data were collected from 123 employees across various industries and analyzed using confirmatory factor analysis. The CFA analysis showed that all items in the final construct had outer loading values above 0.70. In addition, the Cronbach's Alpha and Composite Reliability values for all constructs were above 0.70, and the AVE value exceeded 0.50. Thus, the HWBPWS construct was declared valid and reliable. The results showed that the Indonesian version of the HWBPWS retained 40 fit items across 10 dimensions, with three dimensions removed due to low reliability. All constructs achieved acceptable validity and reliability. These findings provide an evidence-based tool for assessing HR practices that simultaneously improve employee performance and well-being, with important implications for HR management research and practice in Indonesia.